PWE-079 Clinical assessment of operative fitness can identify patients at risk of complications after hepatectomy for malignant disease, but does not correlate with long-term survival. (22nd June 2015) - Ulyett, S; Wiggans, M; Bowles, M; Aroori, S; Briggs, C; Minto, G; Stell, D
Abstract : Introduction: Liver resection is associated with significant morbidity and mortality, and accurate pre-operative assessment of risk is an important part of the pre-operative consultation. Numerous scoring systems exist to assess operative risk, which are rarely used in routine practice. All patients, however, are assessed in out-patient clinic and a subjective assessment of risk is made. Patients thought to be at higher risk of operative complications in our hospital are referred for CPX testing. We wished to establish if clinicians are able to predict patients at greater risk of complications after liver resection. Method: Prospectively collected data on patients undergoing hepatectomy were retrieved from the HPB unit database. From February 2008 to November 2013 patients subjectively anticipated to be at high-risk were selectively referred for CPX. The study group excluded patients with chronic liver disease and biliary obstruction. Operative complications were classified according to the Clavien-Dindo system. Outcomes between the group referred for CPX was compared with control group. Results: During the study period 405 resections were performed on 368 individuals. CPX testing was carried out prior to 101 resections. Median age was 72 and 64 in CPX and non-CPX groups, respectively (P < 0.001). Men accounted for 68% and 46% of CPX and non-CPX patients respectively (P < 0.001). There was no difference in the underlying diagnosis or number of resected liver segments between groups. CPX and non-CPX patients suffered 19 (18.8%) and 28 (9.2%) grade 4–5 complications, respectively (P = 0.009). No difference was seen for grade 3 complications. There was no difference in long-term survival between CPX and non-CPX groups (P = 0.63). Conclusion: This study represents the only attempt to assess clinicians' ability to identify patients at greater risk of complications following hepatectomy. The confirmation that patients identified in this way have approximately 100% greater risk of grade 4–5 complications demonstrates the value of pre-operative counselling by experienced clinicians. Interestingly, patients identified to be lower operative risk do not have improved long-term survival, suggesting disease recurrence and progression are more important determinants of long-term outcome. Disclosure of interest: None Declared.